(untitled) (Journal of the Professional Association for Cactus Development, 1997)
In the last decade, the developed countries have significantly changed their ways of life, and in particular their eating habits. Consumers prefer ready-to-eat foods and a diet that is low in calories, low in cholesterol, low in fat or in other words ?healthy foods?. In accordance with this trend, consumers also want to eat foods with a greater fiber content. Consumers know the relationships between fiber consumption and control of cholesterol, and prevention of illnesses such as diabetes and obesity(Hollingsworth, 1996; Grijspaardt-Vink, 1996; Sloan, 1994). Dietary fiber can also contribute to the prevention, or treatment of illnesses like gastrointestinal disorders, that are associated with a lack of dietary fiber intake. Thus the trend is to search for new natural foods of which fiber is a very appreciated component. This paper will illustrate that cactus cladodes have excellent potential as a new source of fiber in human nutrition.